Measurement of the Z0 → ss- coupling at the SLD - Stängle, Hermann, author; Wilson, Robert J., advisor (Colorado State University. Libraries, 1999)
This dissertation presents a direct measurement of the parity-violating coupling of the Z0 to strange quarks As derived from e+e- collision data containing approximately 550.000 hadronic decavs of polarized Z0 bosons. Data were recorded with the SLC Large Detector (SLD) at the SLAC Linear Collider (SLC) between 1993 and 1998 with an average electron beam polarization of 73% and 74% during the 1993-5 and 1996-8 run periods, respectively. Making use of several unique features of the SLC and SLD, this measurement relies on a new generation particle identification system, the Cherenkov Ring Imaging Detector, to test the Standard Model prediction of universality in the coupling of the Z0 to down-type quarks. Polarized Z0 → ss- events are tagged by the presence in each event hemisphere of a high-momentum K±, K-0s or A0/Ā0 identified using particle identification and/or a mass tag. The background from heavy flavor events is suppressed with the CCD-based vertex detector. The event thrust axis is signed with the strangeness of the tagged particle to point in the direction of the initial s quark. The coupling As is derived from a maximum likelihood fit to the polar angle distributions of the tagged s quark measured with left- and right-handed electron beams. To reduce the model dependence of the measurement, the background from uu- and dd- events as well as the analyzing power of the method for ss- events are constrained from the data. We obtain As = 0.86 ± 0.08(stat.) ± 0.05(syst.). The result is consistent with both the Standard Model prediction and previous bottom quark coupling, Ab, measurements performed by SLD and LEP, and therefore supports the predicted universality of the Z0 to down-type quark couplings.
Keywords: particle physics